MODEL PEMBELAJARAN DEEP LEARNING DALAM PENDIDIKAN INKLUSI:ANALISIS TEORETIS DAN PRAKTIS - Arsani, Arsani; Mardiana, Mardiana; Muftilah, Agnes Sri; Ningsih, Diarti Andra; Nurhayati, R.; Qadrianti, Laeli (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
Education is a crucial part of the national development process, contributing to a country's economic growth. This research aims to examine the optimal implementation of deep learning strategies in the context of inclusive education. In compiling this study, the researchers employed descriptive qualitative methods through a literature review. The findings indicate that the use of a deep learning framework in inclusive settings has proven effective in creating in-depth, meaningful, and adaptive learning processes. Further research is recommended to focus on the development of specific teaching tools and intensive teacher training to optimize the implementation of this strategy in the field.